STUDENT'S PERCEPTION OF HELLO ENGLISH APPLICATION ON STUDENTS VOCABULARY LEARNING - Farida Repelita Waty Kembaren; Meriah Hati Lubis (Universitas Negeri Islam Sumatera Utara, 2022)
Mobile technology quickly attracts new users, providing full features to support language development. One of the tools that plays a key role in the development of mobile language for students is the inclusion of many educational applications. This can improve the practical and structural features of the Mobile Assisted Language Learning (MALL) process. In this case, the researcher uses the mobile app 'Hello English' as a means of communication. The study was designed to determine students 'ideas for using the' Hello English 'program as a way to develop students' skills in developing student vocabulary. In this study, researchers used a list of questions to get ' opinions. This study uses qualitative as a research project. The study was conducted at Junior High School in Ujung Batu Jae, North Padang Lawas. Participants are 25 students who use Hello English. The results showed that most of them gave good ideas about the application because they easily understood the story, were enthusiastic and motivated to learn English, 'Hello English' can eliminate boredom in reading and help them understand the story. Keywords : hello english, student's perception, vocabulary mastery